(3GdJfXje GdbGfhfj dGYGOI GdTQcGJ GdeSGgeI GdYGeI (B-(3OQGSI ebGQfI(B.s - (3SGej eMeO(B, (3GdNQGHTIs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2008)
(3gPG GdcJGH jJfGhd ehVhY GdJfXje GdbGfhfj dGYGOI gjcdI GdTQcGJ GdeSGgeI GdYGeI (B-(3eGgjI GdgjcdI hCSHGHgG , GdhSGFd GdGLQGFjI dGYGOI GdgjcdI , GdhSGFd GdehVhYjI dGYGOI GdgjcdI s
(3HjHGjhZQGajG U(B. 199s
Keywords: (3TQcGJ eSGgeIs; (3bGfhf NGUs